2015
DOI: 10.1111/febs.13531
|View full text |Cite
|
Sign up to set email alerts
|

Repairing the basic defect in cystic fibrosis – one approach is not enough

Abstract: Repairing the basic defect in cystic fibrosis folding of these mutant proteins, allowing their escape from ER-associated degradation and their expression at the cell surface [4].Class III: mutations that include those that disrupt channel regulation through impaired gating. These are mainly mutations located in the NBDs, affecting ATP binding and/or hydrolysis, thus precluding the channel from functioning properly. The prototypical example is G551D (the third most common disease causing mutation present in 4-5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 135 publications
(217 reference statements)
0
31
0
Order By: Relevance
“…It is now 20 years after these studies, and there has been the discovery of a number of pharmacological correctors aimed at treatment of the F508del mutation [25]. For example, compounds have been produced that affect the F508del-CFTR interactome including the proteasome complex that leads to degradation of the protein and chaperones that specifically bind to the F508del-CFTR peptide [13, 26, 27]. …”
Section: Treatments Affecting the Stability Defectmentioning
confidence: 99%
“…It is now 20 years after these studies, and there has been the discovery of a number of pharmacological correctors aimed at treatment of the F508del mutation [25]. For example, compounds have been produced that affect the F508del-CFTR interactome including the proteasome complex that leads to degradation of the protein and chaperones that specifically bind to the F508del-CFTR peptide [13, 26, 27]. …”
Section: Treatments Affecting the Stability Defectmentioning
confidence: 99%
“…More than 120 different mutations of the CFTR gene are known, definitely causing milder or more severe disease (2). The most abundant mutation is the ΔF508 mutation (lack of phenylalanine at position 508) (2,3). The disturbed chloride transport causes less water secretion of the exocrine glands and thus less hydration of all of their products.…”
mentioning
confidence: 99%
“…This study also reported that blocking of endocytosis with DN Rab5a and enhancement of recycling with overexpression of Rab11 is able to promote accumulation of rescued F508del-CFTR at the PM -one of the first studies to report that the late steps of trafficking are amenable to therapeutic modulation to promote mutant protein stability (reviewed in ref. 16). …”
Section: Regulation Of Cftr Membrane Trafficking By Rab Gtpasesmentioning
confidence: 99%
“…In fact, the latest evidence with this latter class of molecules agrees with the concept that the treatment of a pathology as complex as CF will require the combination several therapeutic approaches directed at the several biochemical and physiologic processes that are compromised in CF disease. 16 …”
Section: Rab Proteins As Putative Therapeutic Targetsmentioning
confidence: 99%